ENFORCEMENT OF CUSTOMARY LAW AND NATIONAL LAW IN THE BADUY AND CITOREK INDIGENOUS COMMUNITIES - Gatot Efrianto (Adisam Publisher, 2025)
The purpose of this writing is to provide an explanation of the Baduy and Citorek customs, each of which has many unique cultural values and local wisdom in Indonesia. The Baduy people live in the interior of Banten, and the Sundanese people live in the mountains of Garut. Further study on the characteristics and benefits of each tradition. The Baduy customs are known for their principles of simple living and environmental conservation, while Citorek is famous for its terraced farming that is still practiced to this day. Although they come from various places, they share traditions and noble values that have been passed down from generation to generation. The study of Baduy and Citorek customs offers many lessons about Indonesia's cultural diversity and the importance of preserving heritage for future generations. By learning more about the characteristics of Baduy and Citorek, we can also see how the local community preserves their culture despite the advancing world. This shows that preserving original traditions and culture is very important in facing challenges in the modern era. Local wisdom, which is an important part of the identity of the Indonesian nation, can also be appreciated and absorbed by us. As a result, cultural wisdom such as the Baduy and Citorek customs must continue to be encouraged and supported so that future generations can enjoy their values and the richness of their traditions. A better understanding of local culture helps us appreciate the importance of preserving diversity as part of a rich and varied national identity. Indonesian culture has the ability to evolve and become a valuable heritage for future generations.